Serum neurofilament light chain (NFL) remains unchanged during electroconvulsive therapy. (7th February 2020) - Besse, Matthias; Belz, Michael; Folsche, Thorsten; Vogelgsang, Jonathan; Methfessel, Isabel; Steinacker, Petra; Otto, Markus; Wiltfang, Jens; Zilles, David
Abstract: Objectives: Although there is consistent evidence that electroconvulsive therapy (ECT) is safe and well tolerated by the majority of patients, some authors still accuse ECT to inevitably cause brain damage and permanent memory loss, assertions that may increase patients' worries about a useful treatment. Recently, the measurement of neurofilament light chain (NFL) in peripheral blood was technically implemented, permitting longitudinal analysis of this biomarker for axonal damage. NFL is part of the axonal cytoskeleton and is released into the CSF and peripheral blood in the context of neuronal damage. Methods: In our study, blood from 15 patients with major depressive disorder receiving ECT was collected before the first ECT as well as 24 h and seven days after the last ECT, respectively. NFL concentrations were analysed using the ultrasensitive single molecule array (Simoa) technology. Results: NFL concentrations did not differ between patients and healthy controls, and there was no significant change in NFL levels in the course of ECT. On the contrary, we even found a slight decrease in absolute NFL concentrations. Conclusions: Our study confirms the safety of ECT by using a most sensitive method for the detection of NFL in peripheral blood as a biomarker of neuronal damage.